Erythrocyte aggregation in sudden flow arrest is linked to hyperthermia, hypoxemia, and band 3 availability. (3rd August 2022) - Weber‐Fishkin, Samantha; Seidner, Harrison S.; Gunter, Geoffrey; Frame, Mary D.
Abstract: Background: Erythrocyte aggregation is a phenomenon that is commonly found in several pathological disease states: stroke, myocardial infarction, thermal burn injury, and COVID‐19. Erythrocyte aggregation is characterized by rouleaux, closely packed stacks of cells, forming three‐dimensional structures. Healthy blood flow monodisperses the red blood cells (RBCs) throughout the vasculature; however, in select pathological conditions, involving hyperthermia and hypoxemia, rouleaux formation remains and results in occlusion of microvessels with decreased perfusion. Objectives: Our objective is to address the kinetics of rouleaux formation with sudden cessation of flow in variable temperature and oxygen conditions. Methods: RBCs used in this in vitro system were obtained from healthy human donors. Using a vertical stop‐flow system aligned with a microscope, images were acquired and analyzed for increased variation in grayscale to indicate increased aggregation. The onset of aggregation after sudden cessation of flow was determined at proscribed temperatures (37–49°C) and oxygen (0%, 10%), and in the presence and absence of 4, 4′‐Diisothiocyano‐2, 2′‐stilbenedisulfonic acid (DIDS). Both autologous and homologous plasma were tested. Results: RBCs in autologous plasma aggregate faster and with a higher magnitude with both hyperthermia and hypoxemia. Preventing deoxyhemoglobin from binding to band 3 with DIDS (dissociates the cytoskeleton from the membrane) fully blocks aggregation. Further, RBC aggregation magnitude is greater in autologous plasma. Conclusions: We show that the C‐terminal domain of band 3 plays a pivotal role in RBC aggregation. Further, aggregation is enhanced by hyperthermia and hypoxemia.